Trend Analysis of Project Management Practices in Educational Technology Projects - Hafizah Adnan, Nor; ., . (International Journal of Engineering and Technology, 2018)
The evolution of technology offers abundant opportunities and complexities of how the industry and organizations operate and evolve. Open and distance education has been made possible through the application of modern educational technology. However, educational technology projects are challenged with inadequate project management implementation, insufficient organizational and post-implementation support, and mistake in design and rollout technology. Instructional designers often spend a significant amount of time on instructional design tasks than project management. Whether an instructional designer subscribes to the ADDIE model, the Merrillâ€™s First Principles of Instruction or a model of their own making, these are just frameworks to deliver effective design solutions. Elements of the project management methodology can be embedded in instructional design models for creating engaging learning experiences. Motivated by this concern, this study aims to analyze the decadal trends in research on project management in educational technology projects by conducting a content analysis of peer reviewed journal articles. The number of publications on this topic has increased dramatically over the span of five decades. This study concludes by highlighting the need for instructional designers to possess sound project management skills, enabling them to complete educational products on time, within budget and in conformance with learner needs.Â Â